The Effect of Gross NPF, ZISWAF, and Wadiah Bonus on Mudharabah Income and Firm Size Moderated in Sharia Banking - Aprelia, Nala Widya; Budianto, Eka Wahyu Hestya (Jurnal Cendekia Keuangan, 2025)
Introduction/Main Objectives: This study aims to determine and test the influence of Gross NPF, ZISWAF Fund Receipts, and Wadiah Bonus on Mudharabah Income with Firm Size as a Moderating Variable in Sharia Banking in Indonesia. Background Problems: NPF is an indicator used to measure non-performing financing and the resulting risks that will harm banks. The existence of ZISWAF funds will have a positive impact on economic equity. These challenges are the same as the Wadiah bonus received by customers and come from the provision of Islamic banks as a form of appreciation for believing in banking. Whether or not the solution to a problem is not far from the factor of how the company is in condition, the variable that shows the size of a company is referred to as firm size, which will be described by total assets, sales, employees, and so on. Novelty: This research fills the gap in Islamic bank research in Indonesia. Research Methods: The sample used is the financial report for the 5th quarter of Islamic banking for the 2018.Q1-2023 period. Q3. The technique chosen for sampling is using purposive sampling, with a total sample of 115 Islamic banking financial statements. Panel Data Regression Analysis and Moderated Regression Analysis (MRA) techniques were used in this study with the application of Eviews 12. Finding/Results: Gross NPF and ZISWAF fund receipts have no effect on mudharabah income, while wadi'ah bonus variables have an effect on mudharabah income. Likewise, firm size is not able to moderate the Gross NPF variable and ZISWAF fund receipts on mudharabah income. However, it is able to moderate the influence of wadi'ah bonuses on mudharabah income. Research limitation/implications: In the next study, other moderation variables can be used, such as the health status of the bank in order to determine the influence of other variables on the company.